Influence of atmospheric modes of variability on the limnological characteristics of large lakes south of the Alps: a new emerging paradigm - Salmaso, Nico; Cerasino, Leonardo; Buzzi, F.; Garibaldi, L.; Leoni, B.; Morabito, G.; Rogora, M.; Simona, M. (2012)
Many distinct climate anomalies related to each other over large distances were identified both in the northern and southern hemispheres. Among these, the North Atlantic Oscillation was identified as the most important teleconnection index in the North Atlantic region, with important effects on lacustrine ecosystems in Central and Northern Europe. By converse, no measurable effects were shown on the limnological characteristics of the deep lakes south of the Alps. Recent studies carried out in Lake Garda showed a strong impact on the local climate and limnology of the southern Alpine district of two distinct modes of atmospheric oscillations relevant for the Mediterranean area, namely the East Atlantic pattern (EA) and the Eastern Mediterranean Pattern (EMP). Positive and negative EA, and negative and positive EMP phases are connected with the development of mild and harsh winters, respectively. In this work we analysed the impact of EA and EMP on the largest lakes located at the southern flanks of the Alps (Garda, Iseo, Como, Lugano and Maggiore). The results showed an extended impact of EA and EMP on the winter air temperatures, thermal structure and deep mixing dynamics. In turn, harsh winters and deeper spring mixing depths in lakes Garda, Iseo and Como had a strong and positive influence on the replenishment of epilimnetic phosphorus at spring overturn. Owing to the lower differences in the content of total phosphorus (TP) in the surface and hypolimnetic layers, the effects of a deep mixing on the epilimnetic replenishment of nutrients in Lake Maggiore were less distinct. In Lake Lugano, maximum surface TP fertilisation was observed only during the largest negative (positive) phases of EA (EMP), but without a clear relationship in the whole data range. The implications for the development of phytoplankton will be discussed in relation to the climatic fluctuations and mixing dynamics